Nilai-Nilai Pendidikan Tauhid dalam Novel “Bumi Cinta” Karya Habiburrahman El Shirazy - Rostiani, Herni; Iswanto, Pepe (Tsamratul Fikri | Jurnal Studi Islam, 2019)
Monotheism education is a teaching to know Allah SWT. To be more confident in the One God, Allah must have religious knowledge and education. Education is not only obtained at school or at home, but education can be obtained through novels. One novel that contains the values ​​of monotheism education, namely the novel "Bumi Cinta" (A Novel Builders the Soul) by Habiburrahman El Shirazy. This novel not only contains a story about the beauty of the city of Moscow, but therein are the Qur'anic propositions and the values ​​of monotheism education. The novel "Bumi Cinta" (A Soul-Building Novel) by Habiburrahman El Shirazy is told in interesting language, with Russian quotations also truly able to wash away readers as if they were really in Russia. So it is not boring when read, more importantly about this novel the story in it is very inspiring and motivating. After analyzing the data, the researcher obtained the following conclusions: 1. The novel contained the values ​​of monotheistic education, namely: (a) Uluhiyah Education Values, constituting Allah SWT by the actions of the servants based on taqarrub intentions that are required, (b) Rububiyah's Educational Value, is the servant's belief that Allah SWT is the only God who created this whole creation by himself, (c) Educational Value of al-Asma 'wa ash-Shifat, are the names and attributes of Allah SWT as He established for Himself or what has been determined by His Messenger, 2. The values ​​of monotheism education contained in the novel "Bumi Cinta" (A Novel Soul Builder) by Habiburrahman El Shirazy that are relevant to Islamic education today are: Istiqomah, Istikharah, and istigfhar.